A Healing Garden Therapy Program Exploration in a Hospital Using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) Model: Qualitative Study - Agustina Sri Oktri Hastuti; Christantie Effendy; Herlina Suminarhati (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Staying in the hospital for a long period can affect a patient's psychological condition and may cause stress that slows down recovery. Healing Garden Therapy is a hospital program that can help support recovery, especially for patients with non-communicable diseases.  Therefore, this study aims to explore the implementation of the Healing Garden Therapy program in hospitals using assessment model of Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM). This study used a qualitative exploratory design. The participants consisted of two groups: 10 nurses and 8 non-nursing staff who were involved in the implementation of Healing Garden Therapy Program (HGTP), selected using purposive sampling. Data were collected using recorded Focus Group Discussions (FGDs) and using semi-structured guiding questions. The data were analyzed using Colaizzi's method and presented using the COREQ checklist. The study found four main themes: 1) The main targets of the Healing Garden Therapy Program are patients, families, and visitors; 2) Delivering holistic care; 3) The Healing Garden program has positive impacts and therefore should be reactivated; 4) The Healing Garden Therapy program needs management supports and nurses involvement. The Healing Garden Therapy program has shown positive impacts and should be implemented to support holistic nursing care in hospitals.